Endoscopic Accessories Used for More Advanced Endoluminal Therapeutic Procedures - Hyunsoo Chung (Korean Society of Gastrointestinal Endoscopy, 2017)
Endoscopic accessories describe an extensive variety of auxiliary instruments used for diagnostic and therapeutic endoscopy. Various endoscopic accessories have been developed over the previous few decades and are mostly used for treating neoplastic lesions, such as early gastrointestinal (GI) carcinomas and premalignant lesions. Because of extensive research on natural orifice endoluminal surgery (NOTES) in the early 2000s and recent technological developments, new devices have been developed for various advanced endoluminal therapeutic procedures. In particular, a remarkable development of endoscopic management was achieved in the field of gastroesophageal reflux disease (GERD) and obesity. In both conditions, there is treatment gap between medical and surgical therapy. A large proportion of the patients who do not respond to medical treatment and lifestyle modification, still hesitate to directly undergo surgical treatment. To bridge this gap, endoscopic management has been receiving increasing attention. In this article, I review endoscopic and/or endoluminal devices used for the treatment of GERD and obesity with proposed mechanisms of their function.